2021
DOI: 10.3892/etm.2021.11109
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial endocarditis masked by COVID‑19: A case report

Abstract: Infective endocarditis represents a rare complication among patients infected with severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2); it is often a nosocomial infection and the symptomatology can be masked by respiratory failure symptoms from SARS-CoV-2 bronchopneumonia. Management of patients with severe forms of SARS-COV-2 infection who also have associated infective endocarditis is very difficult, especially in mono-specialty hospitals (such as infectious diseases hospitals) where access to cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…In our study, there was no significant difference in the site of acquisition of infection between community- and healthcare-associated IE. This was consistent with the literature [ 13 ], even though some authors have reported cases of nosocomial IE during long-term hospitalization for SARS-CoV-2 infection [ 15 , 16 ]. In contrast, the proportion of IE related to IV drug use was significantly higher in the pandemic year (Group 2) than in Group 1 (11.8% versus 3.7%) and also higher than that in the literature, which reported a rate of approximately 6.9% [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, there was no significant difference in the site of acquisition of infection between community- and healthcare-associated IE. This was consistent with the literature [ 13 ], even though some authors have reported cases of nosocomial IE during long-term hospitalization for SARS-CoV-2 infection [ 15 , 16 ]. In contrast, the proportion of IE related to IV drug use was significantly higher in the pandemic year (Group 2) than in Group 1 (11.8% versus 3.7%) and also higher than that in the literature, which reported a rate of approximately 6.9% [ 2 ].…”
Section: Discussionsupporting
confidence: 92%
“…The SARS-CoV-2 pandemic had a psychosocial impact and social consequences, which may have promoted the occurrence or decompensation of psychiatric pathologies such as depression, anxiety disorders, and addictions. Moreover, patients who use intravenous drugs may have had more difficulty in accessing sterile equipment during the lockdown period [ 15 , 16 , 17 , 18 , 19 ]. Finally, paradoxically, this population may have had better and priority access to emergency care.…”
Section: Discussionmentioning
confidence: 99%
“…These individual clinical accounts offer valuable insights and anecdotal evidence that can contribute to our understanding of the complex interplay between these distinct yet potentially interrelated conditions. By meticulously examining these real-world cases, researchers and clinicians can identify patterns, trends, and commonalities that indicate a possible association or shared mechanisms [ 42 , 49 - 51 ].…”
Section: Reviewmentioning
confidence: 99%
“…Описано множество случаев инфекционного эндокардита в контексте COVID-19. Например, в Румынии описан случай с 73-летней женщиной, у которой диагностирован инфекционный эндокардит Enterococcus faecium с молниеносным течением после перенесенного COVID-19 [53]. Также группа исследователей заметила увеличение заболеваемости инфекционным эндокардитом во время пандемии COVID-19.…”
Section: присоединение инфекцииunclassified